Lifting Wing in Constructing Tall Buildings —Aerodynamic Testing - Ian Skelton; Peter Demian; Jacqui Glass; Dino Bouchlaghem; Chimay Anumba (Buildings, 2014)
This paper builds on previous research by the authors which determined the global state-of-the-art of constructing tall buildings by surveying the most active specialist tall building professionals around the globe. That research identified the effect of wind on tower cranes as a highly ranked, common critical issue in tall building construction. The research reported here presents a design for a “Lifting Wing,” a uniquely designed shroud which potentially allows the lifting of building materials by a tower crane in higher and more unstable wind conditions, thereby reducing delay on the programmed critical path of a tall building. Wind tunnel tests were undertaken to compare the aerodynamic performance of a scale model of a typical “brick-shaped” construction load (replicating a load profile most commonly lifted via a tower crane) against the aerodynamic performance of the scale model of the Lifting Wing in a range of wind conditions. The data indicate that the Lifting Wing improves the aerodynamic performance by a factor of up to 50%.